A cross-sectional survey to map Clinical Pharmacy Education and Practice in Europe - RABUŞ, ŞULE (SPRINGER, 2022)
Background Clinical activities provided by pharmacists are increasing worldwide, including in Europe. However, an overview of clinical pharmacy education and practice is needed. Aim To map clinical pharmacy (CP) education and practice among European countries. Method A cross-sectional web-based survey led by the Education Committee of the European Society of Clinical Pharmacy (ESCP) was conducted. The survey comprised three domains focusing on: undergraduate education, postgraduate education, and practice. A multi-phased validation process was undertaken, attributing levels of evidence according to the number of information sources for each country. Triangulation was used to seek within country consensus. Main outcome measures included the number of hours of education in CP; existence of a specialization in CP and activities delivered in practice. Results Data from 40 European countries were included (response rate 95.2%). Most respondents (86.8%) agreed with the ESCP definition of CP. Almost every country (94.9%) reported CP topics at the undergraduate level [median number = 65 h/semester (IQR: 2.0-5.6)], including practical teaching [median = 30.0% (IQR: 17.0-42.0)]. At postgraduate level, 92.5% of countries reported PhD programmes including CP and 65.0% mentioned the existence of specific CP master/diploma degrees. Continuous professional development (CPD) courses were also reported by 63.9% of respondents. More than half the countries (52.5%; n = 21) recognized CP as an area of specialization, which for 60.0% of participants was applied solely in the hospital setting. Conclusion Although CP is embedded in education and practice in European countries, there is wide variability in education and practice patterns.
Keywords: Clinical activities; Clinical Pharmacy; ESCP; Pharmacy Education; Pharmacy Practice; Specialization